Leptin and hypothalamic gene expression in early- and late-maturing Bos indicus Nellore heifers - Aline Vaiciunas; Luiz L. Coutinho; Flávio V. Meirelles; Alexandre V. Pires; Luis Felipe P. Silva (Genetics and Molecular Biology, 2008)
We investigated wether early-maturing or late-maturing Bos indicus Nellore heifers produced more leptin mRNA in adipose tissues and altered expression of hypothalamic genes related to leptin signaling. Six prepubertal and six pubertal heifers aged about 34 months and weighing 280 kg to 300 kg each were selected from a population of 100 Nellore heifers. Real-time PCR was used to quantify the expression of the leptin gene (LEP) in adipose tissues and the long isoform of the leptin receptor gene (Ob-Rb), the NK2 homeobox 1 hypothalamic marker gene NKX2-1, the suppressor of cytokine signaling 3 gene (SOCS-3), the neuropeptide Y genes (NPY) and the NPY G-protein coupled receptor genes NPY-Y1 and NPY-Y4 in the hypothalamus. Heifers attaining puberty earlier showed significantly greater LEP expression in adipose tissues (p < 0.05) and there was tissue interaction (p < 0.05). Hypothalamic expression of Ob-Rb, NKX2-1, NPY and SOCS-3 did not differ between groups, but in early-maturing heifers there was a tendency for lower expression of NPY-Y1 (8.3-fold less) and NPY-Y4 (14.3-fold less) compared to late-maturing heifers (p = 0.1). These results suggest that a combination of higher LEP expression, lower NPY-Y1 and NPY-Y4 expression could be a factor in regulating puberty in early-maturing B. indicus heifers.